Lower extremity joint loads in habitual rearfoot and mid/forefoot strike runners with normal and shortened stride lengths - Boyer, E. R.; Derrick, T. R (Journal of Sports Sciences, 2018)
Our purpose was to compare joint loads between habitual rearfoot (hRF) and habitual mid/forefoot strikers (hFF), rearfoot (RFS) and mid/forefoot strike (FFS) patterns, and shorter stride lengths (SLs). Thirty-eight hRF and hFF ran at their normal SL, 5% and 10% shorter, as well as with the opposite foot strike. Three-dimensional ankle, knee, patellofemoral (PF) and hip contact forces were calculated. Nearly all contact forces decreased with a shorter SL (1.2-14.9% relative to preferred SL). In general, hRF had higher PF (hRF-RFS: 10.8 ± 1.4, hFF-FFS: 9.9 ± 2.0 BWs) and hip loads (axial hRF-RFS: -9.9 ± 0.9, hFF-FFS: -9.6 ± 1.0 BWs) than hFF. Many loads were similar between foot strike styles for the two groups, including axial and lateral hip, PF, posterior knee and shear ankle contact forces. Lateral knee and posterior hip contact forces were greater for RFS, and axial ankle and knee contact forces were greater for FFS. The tibia may be under greater loading with a FFS because of these greater axial forces. Summarising, a particular foot strike style does not universally decrease joint contact forces. However, shortening one`s SL 10% decreased nearly all lower extremity contact forces, so it may hold potential to decrease overuse injuries associated with excessive joint loads.